Pirolisis Biomassa Pelepah Sawit Menjadi Bio - Oil Dengan Katalis Natural Zeolit Dealuminated (NZA) - Rajib Azri; Syaiful Bahri; Aman Aman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Petroleum as a primary energy source at this time, increasingly limited supply. Beside the population growth will lead to the increasing need for petroleum. To overcome these problems needed alternative energy sources that can be updated is one of the bio-oil. Bio-oil produced by pyrolysis process using biomass with warming, in the absence of oxygen. The purpose of this study was to determine the effect of variations in the catalyst on the yield of bio-oil produced, knowing the value of density, viscosity, acid number and flash point of bio-oil as well as knowing the chemical components of the bio-oil by GC-MS method. Pyrolysis uses palm frond as much as 50 grams along with 500 ml silinap with NZA catalysts variation of 0%, 1%, 2%, 3%, and 4% w / w with a stirring speed of 300 rpm and a temperature of 320 º C for 120 minutes. In this penelitiam largest yield obtained on the catalyst NZA 3% variation of 44.4%. Characteristics of physical properties obtained are: density of 0.996 g / ml, 11.733 cSt viscosity, acid number 79.34 g NaOH / g sample, as well as the flash point 58 º C. The results of GC-MS analysis, the dominant chemical components in bio-oil are acetic acid (40.90%); methanol (9.60%); methyl ester (2.30%); phenol (32.88%); 2-furancarboxaldehyde (8.98%).Keywords : Bio-oil, Pyrolysis, NZA, Palm Frond